Investigation of the Chemical Compounds, Antioxidant Effect and Therapeutic Properties of Crocus sativus L. (Iridaceae): A Review - Mhamad, Huda J.; Palani, Zirak M. R.; AL-Zubaidy, Adel (CV. Literasi Indonesia, 2025)
Saffron Crocus sativus L. (family Iridaceae) is produced in autumn also, is an expensive spice development in Mediterranean climates It takes between 110,000 and 200,000 flowers to harvest one kilogram of stigmas. Stigmas of Croci Sativa (Croci stigmas) is a pharmaceutical primary source, the important factors that impact the quality are soil and climate more than the quality of saffron is determined by secondary metabolites, including as a culinary addition due to their rich perfume, vivid color, and bitter flavor. However, it is more susceptible to forgery for commercial gain, causing danger to public health. The more crucial criterion for identifying crocin concentration is the property of saffron. A new source of antioxidants is the usual medication for depression. Crocus sativus, the central nervous system, depression, dopamine, the dopaminergic and serotonergic systems, picrocrocin, phytotherapy, neurotransmitters, safranal, saffron, serotonin, and physiologically active chemicals are all associated with antidepressant action. It has also been consumed in conventional medicine to handle a range of illnesses, including inflammatory and neurological problems. Saffron includes critical minerals and vitamins. Saffron's anti-aging and anti-oxidant properties make it popular in numerous regions around the globe. Furthermore, the capacity of crocetin, saffron, and crocin to lower the deleterious drug modulator effects of chemotherapeutic components was revealed. Properties saffron and its extract were found to be low- or non-toxic. The aim of this study for show a more therapeutic effect also how to use it to treat disease and produce saffron for medicine.